Food Security in Venezuela: From Policies to Facts - Rodríguez García, Janet J. (Frontiers in Sustainable Food Systems, 2021)
In 1948, The Right to Food is recognised at The General Assembly of the United Nations by the declaration of Human Rights. The Venezuelan Constitution of 1999 explicitly states for the first time in Article 305, Food Security. Subsequently, in Venezuela, various laws and regulations were decreed to promote the right to food of the population. However, despite these laws, nowadays, two decades after the right to food was established in the Constitution, it was found that in Venezuela the rate of malnutrition is high The Objective of this work is to show that decreeing many laws related to food and nutrition is not enough to reduce this scourge, nor are they a guarantee to improve the Food and Nutrition Security of the people.